Photo-isomerization and light-modulated aggregation behavior of azobenzene-based ionic liquids in aqueous solutions. Issue 71 (18th September 2017) - Li, Zhiyong; Wang, Huiyong; Chu, Mengen; Guan, Pengxin; Zhao, Yang; Zhao, Yuling; Wang, Jianji
Abstract : ILs with an azobenzene-group at the end of the alkyl chain could form micelles; UV/vis irradiation only changed the size of the aggregates. Abstract : Light modulation of the isomerization and aggregation behavior of ionic liquids in aqueous solution is of great importance from a fundamental and technical point of view. In this work, 4 kinds of azobenzene-based photoresponsive ionic liquids 2-hydroxyethyl-dimethyl-[10-(4-phenylazo-phenoxy)-decyl]-ammonium bromide (ChoC10 Azo), 2-hydroxyethyl-dimethyl-[6-(4-phenylazo-phenoxy)-hexyl]-ammonium bromide (ChoC6 Azo), 2-hydroxyethyl-dimethyl-[4-(4-phenylazo-phenoxy)-butyl]-ammonium bromide (ChoC4 Azo) and 2-hydroxyethyl-dimethyl-[2-(4-phenylazo-phenoxy)-ethyl]-ammonium bromide (ChoC2 Azo) were designed, synthesized and characterized. The photo-isomerization and light modulation of the aggregation behavior of these ionic liquids were investigated in water using UV-vis spectroscopy, conductivity, dynamic light scattering and small-angle X-ray scattering measurements. The results showed that these ionic liquids had rapid photo-responsive performance, and their photoisomerization efficiencies were greater than 83% after 5 s of UV irradiation. The equilibrium time of the isomerization reaction was about 30 s for ChoC6 Azo, ChoC4 Azo and ChoC2 Azo, and about 10 min for ChoC10 Azo. However, there was no significant difference between the equilibrium isomerization efficiencies of these materials. In addition, only ChoC10 Azo could form micelles in water among the studied ionic liquids, UV/visible light irradiation only changed the size of its aggregates, but could not change its structure. The results have been used to understand the effect of azobenzene group position and alkyl chain length in the ionic liquids on the photoisomerization and self-assembly of the azobenzene-based ionic liquids in aqueous solutions.